Hf isotopic composition of single zircons from Neoproterozoic arc volcanics and post-collision granites, Eastern Desert of Egypt: Implications for crustal growth and recycling in the Arabian-Nubian Shield - Ali, K.; Wilde, Simon; Stern, R.; Moghazi, A.; Ameen, S. (Elsevier BV, 2013)
Zircon Hf isotopic compositions for Neoproterozoic igneous rocks in the Central Eastern Desert of Egypt are presented and interpreted. The Humr Akarim (633 ± 7 and 603 ± 9 Ma)–Humrat Mukbid (625 ± 8 and619 ± 8 Ma) plutons are Early Ediacaran post-collsional subsolvus granites. Their zircon ages range from0.57 to 0.71 Ga, with high positive Hf(T) values of +4.0 to +11.9. Hf model ages (Hf-TDMc) of 0.81–1.3 Ga, are close to the U–Pb crystallization ages. These isotopic characteristics, along with published whole-rock Nd isotopic data, indicate that the protoliths were juvenile. The Wadi Kareim and Wadi El-Dabbah metavolcano-sedimentary rocks are Cryogenian (~750 Ma) arc-related metabasalts, meta-andesites and meta-tuffs. Their U–Pb zircon age populations range between 0.7–0.9, 0.9–1.5 Ga and 2.0–3.0 Ga. The youngest group represents magmatic zircons in the metavolcanics or reworked Neoproterozoic rocks in the metasediments. The 0.9–1.5 Ga and 2.0–3.0 Ga age groups are similar to those in pre-Neoproterozoic rocks that surround the Arabian-Nubian Shield and represent inherited or older detrital grains. The highly variable εHf(T) values (+23.5 to -35.0) and Hf-TDMc ages (0.78–3.8 Ga) of Neoproterozoic zircons indicate that at least some of these magmas interacted with a pre-Neoproterozoic crustal source.